Fiscal Imbalances, Capital Inflows, and the Real Exchange Rate : The Case of Turkey - Ucer, E. (IMF Working Papers; Working Paper ;, 1997)
This paper examines the links between fiscal policy, capital inflows, and the real exchange rate in Turkey since the late 1980s. After an overview of recent macroeconomic developments in Turkey, a vector autoregression model is estimated linking government spending, interest rate differentials, capital inflows, and the temporary component of the real exchange rate. Positive shocks to government spending and capital inflows lead to an appreciation of the temporary component of the real exchange rate, whereas positive shocks to the uncovered interest rate differential lead to a capital inflow and an appreciation of the temporary component of the real exchange rate. The findings highlight the role of fiscal adjustment in restoring macroeconomic stability.